A Social Exclusion Manipulation Interacts with Acquired Capability for Suicide to Predict Self-Aggressive Behaviors. Issue 1 (2nd January 2018) - Hames, Jennifer L.; Rogers, Megan L.; Silva, Caroline; Ribeiro, Jessica D.; Teale, Nadia E.; Joiner, Thomas E.
Abstract : The interpersonal theory of suicide posits that individuals who simultaneously experience high levels of thwarted belongingness, perceived burdensomeness, and acquired capability for suicide are at high risk for a lethal or near-lethal suicide attempt. Although supported by self-report studies, no study has examined facets of the theory experimentally. The present study aimed to examine the belongingness and capability components of the theory by testing whether experimentally manipulated social exclusion interacts with self-reported acquired capability to predict higher self-administered shock levels on a self-aggression paradigm. A sample of 253 students completed self-report measures and were then randomly assigned to a social exclusion manipulation condition (future alone, future belonging, no feedback). Participants then participated in the self-aggression paradigm. The positive association between acquired capability and self-aggression was strongest among participants in the future alone social exclusion condition. In those assigned to the future belonging or no feedback conditions, the association between acquired capability and self-aggression was non-significant. These findings provide modest experimental support for the interpersonal theory of suicide and highlight a potential mechanism through which social exclusion may impact suicide risk. Limitations and future research directions are discussed.